Survival of Firms during Economic Crisis - Bosio, Erica; Djankov, Simeon; Jolevski, Filip; Ramalho, Rita (World Bank, Washington, DC, 2020)
This paper estimates the survival time of nearly 7,000 firms in a dozen high-income and middle-income countries in a scenario of extreme economic distress, using the World Bank's Enterprises Surveys. Under the assumption that firms have no incoming revenues and cover only fixed costs, the median survival time across industries ranges within 8 to 19 weeks, while on average firms have liquidity to survive between 12 and 38 weeks. Schumpeter's theory of creative destruction is not corroborated in the data, as potential exit is not predicated on the size of firms, their age, or their productivity.